2013
DOI: 10.1111/jfs.12021
|View full text |Cite
|
Sign up to set email alerts
|

Nisin‐Loaded Chitosan/Alginate Nanoparticles: A Hopeful Hybrid Biopreservative

Abstract: To improve the deficiencies concerning the physicochemical instability of nisin, a hybrid of nisin at concentration of 450 IU/mL with chitosan/alginate nanoparticles was prepared. Antibacterial strength of the hybrid was compared with free nisin against Listeria monocytogenes ATCC 25923 and Staphylococcus aureus ATCC 19117 in ultra filtered (UF) Feta cheese. The effects of nisin and the nisin-loaded nanoparticles on the chemical composition, rheological parameters, color indices and sensory attributes of UF Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 31 publications
0
22
0
1
Order By: Relevance
“…The application of foodgrade biopolymers for encapsulating, protecting and delivery of antimicrobial peptides is an alternative way. Nisin loaded-micro or nanocapsules were prepared using chitosan/carrageenan (Chopra, Kaur, Bernela, & Thakur, 2014) chitosan/alginate (Zohri et al, 2013), alginate/cellulose (Huq, Riedl, Bouchard, Salmieri, & Lacroix, 2014), alginate/pectin (Khaksar et al, 2014) and alginate/ guar gum (Narsaiah, Jha, Wilson, Mandge, & Manikantan, 2014) biopolymer systems.…”
Section: Introductionmentioning
confidence: 99%
“…The application of foodgrade biopolymers for encapsulating, protecting and delivery of antimicrobial peptides is an alternative way. Nisin loaded-micro or nanocapsules were prepared using chitosan/carrageenan (Chopra, Kaur, Bernela, & Thakur, 2014) chitosan/alginate (Zohri et al, 2013), alginate/cellulose (Huq, Riedl, Bouchard, Salmieri, & Lacroix, 2014), alginate/pectin (Khaksar et al, 2014) and alginate/ guar gum (Narsaiah, Jha, Wilson, Mandge, & Manikantan, 2014) biopolymer systems.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to increase the shelf-life of cheese nisin is used. Interestingly, Zohri et al (2013) found that nisin loaded chitosan nanoparticles can be used for the preservation of cheese. Other antimicrobial peptides used in the biopreservation of dairy products are Pediocin ACH.…”
Section: Preservation Of Cheese and Yogurtmentioning
confidence: 99%
“…They suggested that the ratio of nisin to polymer is important in determining antimicrobial activity that should be monitored and optimized. In another study, Zohri et al (2013) further investigated nisin-loaded chitosan/alginate against L. monocytogenes ATCC nanoparticles were able to decrease the population of S. aureus and L. monocytogenes up to 5-and 7-fold on a logarithmic scale in comparison to free nisin, respectively. Interestingly, the sensory and physicochemical features of ultra-filtered feta cheese were not adversely affected but significantly improved by using nisin-loaded nanoparticles compared to free nisin.…”
Section: Nanoparticlesmentioning
confidence: 98%
“…Nanoparticle system have the potential to alleviate some of the global food supply issues, i.e., increased food shelf life, improvement in food safety and security and minimization of food spoilage(Hannon, Kerry, Cruz-Romero, Morris, & Cummins, 2015). The importance of nanotechnology in food science is recognized by a number of groups worldwide(Berekaa, 2015;Ramachandraiah, Han, & Chin, 2015;Zohri et al, 2013). Numerous approaches related to nanotechnology have been used to enhance the antimicrobial efficacy of preservatives, physically stability, shelf life, biocompatibility and biodegradability and ensure the availability of delivery systems at low cost(Figure 5).…”
mentioning
confidence: 98%